Robust Sparse Arrays with Multiple-Fold Redundant Difference Coarrays - Zhu, Dong; Li, Gang (2019 IEEE International Conference on Signal, Information and Data Processing (ICSIDP), 2019)
Spares arrays can attain O(N^{2}) degrees of freedom (DOF) usingonly N physical sensors, which profits from the O(N^{2}) length of the central uniform linear array (ULA) segment in their difference coarray (DCA). To obtain the optimal DOF performance, the single-fold redundant DCA (that is, each element of DCA occurs as only once as possible) is persistently pursued in array design. Such a criterion inevitably leads this O(N^{2}) ULA segment susceptible to sensor failures, which is a crucial issue concerning array/DCA robustness (or system reliability) in practical applications. That is quite serious for minimum/low-redundancy, nested, and coprime configurations as well as their variations. This paper introduces a novel sparse array geometry, named multiple-fold redundancy array (MFRA), exploiting element redundancies of the DCA. The MFRA is more robust to sensor failures than the aforementioned sparse arrays, for which the concepts of quasi-essentialness and reliability is introduced. Several numerical examples are presented to demonstrate the MFRA's robustness to sensor failures.